A Curse upon the Nation : Race, Freedom, and Extermination in America and the Atlantic World - Lewis, Kay Wright, 1958- (Book collections on Project MUSE., 2017)
"From the inception of slavery as a pillar of the Atlantic World economy, both Europeans and Africans feared their mass extermination by the other in a race war. In the United States, says Kay Wright Lewis, this ingrained dread nourished a preoccupation with slave rebellions and would later help fuel the Civil War, thwart the aims of Reconstruction, justify Jim Crow, and even inform civil rights movement strategy. And yet, says Lewis, the historiography of slavery is all but silent on extermination as a category of analysis. Moreover, little of the existing sparse scholarship interrogates the black perspective on extermination. A Curse upon the Nation addresses both of these issues."--Provided by publisher